2012
DOI: 10.1021/ic201309k
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, X-ray Crystal Structures, and Optical, Fluorescence, and Nonlinear Optical Characterizations of Diphenylphosphino-Substituted Bithiophenes

Abstract: A series of bithiophene derivatives that are either symmetrically disubstituted with two Ph(2)(X)P groups (X = O, S, Se) or monosubstituted with one Ph(2)(X)P group (X = O, S, Se) and an organic functional group (H, CHO, CH(2)OH, CO(2)Me) have been synthesized. The X-ray crystal structures of Ph(2)(Se)P(C(4)H(2)S)(2)P(Se)Ph(2), Ph(2)(O)P(C(4)H(2)S)(2)H, Ph(2)(S)P(C(4)H(2)S)(2)H, and Ph(2)(O)P(C(4)H(2)S)(2)CH(2)OH exhibit very different solid-state structures depending on the type of intermolecular π-π interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 40 publications
5
32
1
Order By: Relevance
“…These values are also very similar to that of PhP(Se)[ O (CH 2 ) 3 O ] (| 1 J PSe | = 876 Hz) indicating that replacing a phenyl group with a bithienyl group only slightly reduces the s‐character of the phosphorus. This behavior is analogous to that which has been observed with Ph 2 P(Se)Ar systems [Ar = Ph, | 1 J PSe | = 732; Ar = H(C 4 H 2 S) 2 , | 1 J PSe | = 735 Hz] , . The | 1 J PSe |s of pdP(Se)T 2 H and pdP(Se)T 2 P(Se)pd are larger than those of Ph 2 P(Se)T 2 H and Ph 2 P(Se)T 2 P(Se)Ph 2 (735 Hz and 739 Hz, respectively) and are slightly smaller than those of the bpP(Se)T 2 H and bpP(Se)T 2 P(Se)bp , .…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…These values are also very similar to that of PhP(Se)[ O (CH 2 ) 3 O ] (| 1 J PSe | = 876 Hz) indicating that replacing a phenyl group with a bithienyl group only slightly reduces the s‐character of the phosphorus. This behavior is analogous to that which has been observed with Ph 2 P(Se)Ar systems [Ar = Ph, | 1 J PSe | = 732; Ar = H(C 4 H 2 S) 2 , | 1 J PSe | = 735 Hz] , . The | 1 J PSe |s of pdP(Se)T 2 H and pdP(Se)T 2 P(Se)pd are larger than those of Ph 2 P(Se)T 2 H and Ph 2 P(Se)T 2 P(Se)Ph 2 (735 Hz and 739 Hz, respectively) and are slightly smaller than those of the bpP(Se)T 2 H and bpP(Se)T 2 P(Se)bp , .…”
Section: Resultssupporting
confidence: 78%
“…The conformation of the major component in both compounds is the anti‐periplanar conformation (≈ 83 %). Both syn‐periplanar and anti‐periplanar conformations are observed for bithiophenes monosubstituted with phosphines, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research group has recently reported that solutions of phosphine‐substituted bithiophenes and terthiophenes of the types Ph 2 P(X)(C 4 H 2 S) n P(X)Ph 2 and Ph 2 P(X)(C 4 H 2 S) n H (X = O, S, Se; n = 2, 3) show strong narrow band NLA at wavelengths across the violet‐blue spectral region . The phosphine‐substituted bithiophenes are particularly impressive because they combine strong NLA with high solubilities and high linear transmittances at wavelengths from 420 to 480 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, UV/visible and fluorescence spectroscopies have been used to evaluate the linear optical properties of solutions of the 2,2′‐bithienyl‐5‐yl substituted polyphosphonates, and the nonlinear optical properties have been evaluated using nonlinear transmittance measurements at 430 nm with a 27 ps laser pulse. The results from these studies are compared with those from our previous studies of molecular phosphonate‐substituted thiophenes …”
Section: Introductionmentioning
confidence: 99%